The level of psychological combustion among teachers and its reflection on the lesson of physical education and sports - salem.lakhdar (sports creativity, 2025)
The title of our study was the level of psychological combustion among the teachers and its reflection on the progress of the physical and sports education class in the state of M’sila. One of the objectives of this study was to reveal the level of reflection of both emotional stress and cold feelings of teachers on the course of physical and sports education . The problem of the study is to what level the psychological burning of teachers reflected on the course of physical education and sports. The hypotheses of this study was that Emotional stress and cold feelings among physical and sports education teachers are largely reflected in the progress of the course. The study sample was a simple random sample of 50 professors out of 123 professors from the indigenous community. This study used the descriptive analytical approach for its relevance to this study and the study tool was a questionnaire for teachers of physical education and sports. The results revealed that the level of psychological combustion , emotional stress and cold feelings among the teachers reflected significantly on the course of physical education and sports